The Trend of Hijrah: New Construction of Urban Millennial Muslim Identity in Indonesia - Farchan, Yusa'; Rosharlianti, Zulfa (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2021)
The emergence of the hijrah movement in Indonesia, both in public and virtual public spaces, marks the revival of the spirit of Islam in the country. This study examines the following issues: how do urban millennial Muslim communities interpret hijrah?; what is the new construction of urban millennial Muslim identity in Indonesia?; and what is the tendency of the preferences of urban millennial Muslims towards the literacy of Islamic da'wah content? This study uses qualitative methods. The survey population was millennial Indonesian urban Muslims, while the study sample consisted of 110 urban millennial Muslims in the Greater Jakarta area. The results of the study indicate several things. First, the millennial generation of urban Muslims interpret hijrah as